Efeito do laser em baixa intensidade sobre a proliferação, adesão e expressão de Runx2 em osteoblastos cultivados na presença de LPS - Teixeira, Victor Perez (2011)
The tissue destruction associated with bone infection is related to the constituents of infectious microorganisms, their products and the activation of secretory cells of the tissue itself and the immune system. The lipopolysaccharide (LPS), wall component of gram-negative bacteria, was the first whose potent ability to induce bone resorption was demonstrated. On the other hand, the low level laser therapy (LLLT) has been used in bone tissue in order to accelerate the repair process. Thus, the objective of this study was to evaluate the effects of LLLT on cell parameters important in the process of bone repair front of infection. To this end, the osteoblast lineage OSTEO-1 (derived from rat calvaria), grown in the presence of LPS (E. coli) were irradiated with LLLT (Ga-Al-As, 780 nm, 10 mW, 12s, 0.12 J , 3 J/cm2). Cultures irradiated and not irradiated (control) were subjected to proliferation assays at 1, 3 and 5 days (MTT) and adhesion after 20, 40 and 60 minutes (MTT). In addition, the gene expression of the transcription factor run-related (Runx2) was assessed after 24 h using the polymerase chain reaction (PCR) in real time. The results showed no statistically significant differences in relation to cell proliferation and the expression of Runx2. As for cell adhesion LPS decreased the adhesion in the groups cultured in the presence of concentrations of 1 and 10 μg/mL after 20 min. and the concentration of 10 μg/mL after 40 and 60 min.. In all periods evaluated LLLT was not able to change this trend.